Postnatal alterations in GABAB receptor tone produce sensorimotor gating deficits and protein level differences in adulthood. Issue 41 (12th October 2014) - Bolton, Monica M.; Heaney, Chelcie F.; Murtishaw, Andrew S.; Sabbagh, Jonathan J.; Magcalas, Christy M.; Kinney, Jefferson W.
Abstract: The GABA transmitter system plays a vital role in modulating synaptic formation and activity during development. The GABAB receptor subtype in particular has been implicated in cell migration, promotion of neuronal differentiation, neurite outgrowth, and synapse formation but it's role in development is not well characterized. In order to investigate the effects of brief alterations in GABAB signaling in development, we administered to rats the GABAB agonist baclofen (2.0 mg/kg) or antagonist phaclofen (0.3 mg/kg) on postnatal days 7, 9, and 12, and evaluated sensorimotor gating in adulthood. We also examined tissue for changes in multiple proteins associated with GABAB receptor function and proteins associated with synapse formation. Our data indicate that early postnatal alterations to GABAB receptor‐mediated signaling produced sex differences in sensorimotor gating in adulthood. Additionally, we found differences in GABAB receptor subunits and kalirin protein levels in the brain versus saline treated controls. Our data demonstrate that a subtle alteration in GABAB receptor function in early postnatal life induces changes that persist into adulthood.